Empowerment of Karang Taruna Cibubur Members to Increase Creativity Through Digital Video Optimization Training: Pemberdayaan Remaja Karang Taruna Cibubur Dalam Rangka Meningkatkan Kreativitas Melalui Pelatihan Optimalisasi Video Digital - Adinugroho, Prasetyo; Trikusumaningtias, Intan; Permana, Restiawan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
As digital technology develops, everyone must have the skills to apply all existing technology. Nowadays, advances in internet technology, especially social media, are quite rapid in providing whatever information we need. Human resources who are skilled in optimizing social media are very necessary in every organization or company. In the East Jakarta area, specifically in Cibubur, there is Karang Taruna, a social institution that serves as a forum for young people to be creative and help empowering the community. On this occasion, Pakuan University collaborated with the organization of Karang Taruna Kelurahan Cibubur in digital video optimization training activities. Aims to improve the skills of Karang Taruna Kelurahan Cibubur members in using digital video for documentation and publication purposes by standardizing information about the institution's activities. So that the long-term goal of establishing cooperation with all existing stakeholders is effective, this training will be carried out in the period from December 2023 to March 2024. This community service activity runs smoothly, the beneficiaries hope that there will be similar activities but with different material. . The participants' enthusiasm in paying attention to the material presented, actively asking questions during the question-and-answer session, and demonstrating according to the resource person's directions proved that this activity was effective